Investigation of the change of the shopping mall’s space organization in Istanbul - Ozorhon, Guliz; Ozorhon, Ilker Fatih (Journal of Architecture and Urbanism, 2014)
Within the scope of this article shopping malls were discussed as a building type and the evolution of a building type was tried to be witnessed within a twenty-five year period by comparing the early and late examples of shopping malls in Istanbul. The change of Istanbul’s shopping culture / spaces and the inclusion of shopping centers into the practice of architecture as a building type are briefly mentioned . Each of the selected malls were separately examined in terms of location, concept, space organization and other functions included, and in the fourth section both early and late examples were evaluated together in the same terms with a holistic perspective. The effect of shopping malls, the number of which constantly increases in Istanbul, on the city and its architecture is highly important. These massive bodies of buildings play a significant role in the formation and even definition of the new settlement areas of the city, and generate new areas of attraction. Due to these reasons, from location to architectural characteristic, from schedule to interior quality, they need to be designed punctiliously and with the consideration of the effects at all levels.